HEARING LOSS PATIENTS` TREATMENT APPROACHES, MENTAL HEALTH ISSUES, AND SOCIAL ORAL PATHOLOGIES- part 2-treatment plan - Lucian Stefan Burlea; Liana Aminov; Veronica Serban Pintiliciuc; Ovidiu Stamatin; Tudor Hamburda; Laura Elisabeta Checheriță (Romanian Journal of Oral Rehabilitation, 2024)
Hearing loss (HL) is the third most prevalent chronic health problem among older adults and is quite common in our study group research. Our study wants to illustrate the research on the connection between HL and depression as well as the therapeutic ramifications for diagnosing and treating comorbid like intraoral rehabilitation, HL, and mental disorders also.